Estimation of psycho-physiological functions of a person and operator work in extreme conditions - Білошицький, П.В.; Ключко, О.М.; Макаренко, М.В. (Proceedings of National Aviation University (archive), 2022)
Some methods and results of psycho-physiological human functions investigation in mountain conditions are given. These results form the base of developed approaches for professional selection of special contingents for the work in extreme conditions. Mathematic model for reliability of human nervous system functioning in extreme conditions is suggested.